Analysis of Public Service Effectiveness in the Implementation of Mobile JKN Application in Deli Serdang Regency - Dalimunthe, Nurhidayah; Adelia, Cyndi; Maulidia, Diva; Arihan, Reva Putri; Febrianti, Dina; Irawan (CV Raskha Media Group, 2025)
The development of information technology is driving the transformation of public services, including digital-based health services. The Social Security Administering Agency (BPJS Kesehatan) launched the Mobile JKN application as a means to facilitate independent access to National Health Insurance (JKN) services. This study aims to analyze the effectiveness of public services through the implementation of the Mobile JKN application in Deli Serdang Regency. This study uses a conceptual approach (conceptual paper) that aims to analyze the effectiveness of public services in the implementation of the Mobile JKN application in Deli Serdang Regency. Research data was obtained through a literature review that includes books, journals, policy reports, and scientific articles related to digital public services. This study integrates the concept of public service effectiveness according to the New Public Service Principles theory and the information system success model according to the DeLone and McLean theory in one conceptual framework. The results of the study indicate that the implementation of the Mobile JKN application has been assessed as effective in digital-based public services to improve efficiency, accountability and transparency of health services to the public.